Does a hypnosis session reduce the required propofol dose during closed-loop anaesthesia induction?: A randomised controlled trial. Issue 9 (September 2018) - Bataille, Aurélien; Guirimand, Avit; Szekely, Barbara; Michel-Cherqui, Mireille; Dumans, Virginie; Liu, Ngai; Chazot, Thierry; Fischler, Marc; Le Guen, Morgan
Abstract : BACKGROUND: Hypnosis has a positive effect on peri-operative anxiety and pain. OBJECTIVE: The objective of this study was to assess the impact of a formal deep hypnosis session on the consumption of propofol for anaesthetic induction using automated administration of propofol guided by the bispectral index (BIS) in a closed loop. DESIGN: A 1 : 1 randomised, usual-care-controlled, single-centre trial. SETTING: Tertiary care centre in France from April 2014 to December 2015. PATIENTS: Female adult patients scheduled for outpatient gynaecological surgery under general anaesthesia. INTERVENTION: Before surgery, patients were randomised to receive either a deep hypnosis session or routine care. Anaesthetic induction was performed automatically by propofol without opioids and was assisted by the BIS in a closed loop. MAIN OUTCOME MEASURES: The primary endpoint was the propofol dose required for anaesthesia induction, defined as a BIS less than 60 for at least 30 s. RESULTS: Data for 31 patients in the hypnosis group and 35 in the control group were analysed. There was no evidence of a difference in the mean required propofol dose for anaesthetic induction between the hypnosis and the control groups (2.06 mg kg −1 (95% confidence interval [1.68 to 2.43]) versus 1.79 mg kg −1 (95% CI [1.54 to 2.03]), P = 0.25, respectively). CONCLUSION: The current study, which was designed to determine the effect of a deep hypnosis session on anaesthesia induction using an automated tool for propofol administration, failed to detect a difference in the required dose of propofol. TRIAL REGISTRATION: ClinicalTrials.gov, NCT02249364.